A Wavelet based method to characterize electrical insulators under partial discharges - Paredes, José; Luzardo, Ender; Briceño, Hildemaro (Rev. Téc. Fac. Ing. Univ. Zulia)
This paper introduces a wavelet packet based method to characterize electricaI insulators under partial discharges. The proposed method applies the wavelet packet decomposition (WPD) on the insulator’s voltage signal, experimentally obtained when the electrical isolator is energized with high voltage. The wavelet coefficients outputted by the WPD are reorganized as a two-dimensional array, and well defined patterns are found that allow us to characterize electrical insulators under different working condition. In particular, the electrical insulators are exposed to different conditions of humidity and contamination similar to those found on air transmission Iines.